The Important Of Description Dive Spot Characteristic For the Development of Tourism Attractions: A Case Study in Bunaken National Park, North Sulawesi, Indonesia - Jeanlly A. Solang (Faculty of Economics and Business, University of Mataram, 2024)
This paper aims to describe the characteristics of diving spots on the island of Bunaken for the purpose of making it a tourist attraction. So far, diving tourists who do diving activities have never received an explanation related to what biota and mammals are located at each dive point. Though this information is very useful for the development of more unique tourist attractions. The method used in this paper is to conduct a survey (non-experimental) combined with direct perception at the writing location and identification by combining knowledge-based methods. Bunaken National Park has 120 dive points with varying depths ranging from 1,344 meters. However, this study only took 16 dive points, specifically around the island of Bunaken. The results showed that each point has unique species of marine biota and mammals, then the average is also in the location of underwater great walls, which are also called hanging walls, or giant vertical coral walls.